A18 BUILDING BETTER ENTEROIDS: A NOVEL STRATEGY FOR ENRICHING SECRETORY EPITHELIAL CELL SUBTYPES. (26th February 2020) - Davies, E E; Crowley, S M; Tsai, K; Diaz Gomez, M; Han, X; Vallance, B
Abstract: Background: Inflammatory bowel diseases (IBD) are chronic gastrointestinal disorders that affect more than 270, 000 Canadians, including over 7, 000 children. Inflammation arising from IBD severely damages intestinal epithelial cells (IECs), however their role in disease pathogenesis is not fully understood, in part due to a lack of in vitro systems that recapitulate the epithelium's complex cellular composition. Enteroids are an in vitro model where primary IECs are isolated and cultured as 3D 'mini guts.' They offer distinct advantages over cell lines, however current protocols generate enteroids primarily composed of enterocytes that seldom contain rarer IEC subtypes (goblet, enteroendocrine, tuft and Paneth cells). These cells are responsible for the gut's mucus, antimicrobial and hormone secretory functions, yet their role in the pathophysiology of IBD is unclear. Aims: Manipulate cell differentiation pathways in mouse and human enteroids to increase the prevalence of secretory IECs, as well as determine if enteroids derived from pediatric IBD patients exhibit impaired responses to differentiation treatments. Methods: Mouse enteroids were derived from ileal, cecal and colonic crypts of C57BL/6 mice while human enteroids were isolated from healthy or pediatric IBD patient intestinal biopsies. Enteroids were initially supplemented with Wnt signaling activators and the extracellular matrix modified to enhance enteroid culture "stemness". Differentiation was induced by growth media modulation of the Notch and Wnt signaling pathways. Enteroids were analyzed via flow cytometry to quantify expression of secretory cell markers, while immunofluorescent and Peroidic acid Schiff/Alcian Blue staining was used to visualize goblet cells. Results: "Stem" treatment potentiated Wnt signaling and enhanced enteroid "stemness" as measured by Lgr5 and CD44 expression. Comparatively, differentiation of these "stem" enteroids led to a larger relative increase in secretory markers. Differentiation treatment increased expression of goblet cell markers (Muc2 and lectin) in the "stem" treated mouse cecal and colonic enteroids, but not in ileal enteroids. Notch inhibition produced increased expression of lysozyme, a Paneth cell marker, in all enteroids. A similar increase in secretory cell numbers was observed in control human enteroids following differentiation treatment. In contrast, enteroids derived from pediatric IBD patients displayed irregular differentation responses to treatment. Conclusions: We demonstrate that manipulation of cell differentiation pathways increases the number of secretory IEC subtypes within enteroids. Furthermore, these pro-secretory cell responses differ in IBD patient enteroids, indicating that an alteration of the targeted cell signaling pathways may be linked to IBD pathogenesis. Funding Agencies: CCC, CIHRBCCHRI Summer Studentship